Nanowire toughened ultrahigh-temperature anti-ablation coating and preparation method thereof

By depositing PyC inner coating and HfCnw enhanced SiC/HfC outer coating on the surface of C/C composite, the problem of easy oxidation and thermal mismatch of C/C materials at high temperatures is solved, and its anti-oxidation and burn-resistant are improved The corrosion performance extends its service life in harsh environments.

CN119161207APending Publication Date: 2024-12-20湖北瑞宇空天高新技术有限公司

Patent Information

Application Number
CN202411438734.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

C/C composites are prone to oxidation under high temperature environments, and the traditional coating is not closely combined with the substrate, resulting in thermal mismatch residual stress and ablation problems, limiting their application in the aerospace field.

Method used

The PyC inner coating was deposited on the surface of the C/C blank, and HfCnw was deposited by catalytic CVD method, and finally the SiC/HfC outer coating was prepared externally, which enhanced the flush resistance of the coating by HfCnw.

Benefits of technology

It significantly improves the oxidation resistance of C/C composite materials and the bonding strength of the coating and substrate, and extends the service life in high-temperature oxygen-containing gas flow environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

The invention relates to an ultra-high-temperature ceramic nanowire toughened ultra-high-temperature anti-ablation coating and a preparation method thereof. The anti-ablation capability of C / C can be further improved. The process method comprises the following steps: firstly, preparing a PyC inner coating on a C / C green body by utilizing an isothermal CVD (Chemical Vapor Deposition) method; a catalyst is introduced to the surface of the PyC inner coating by brushing a Ni (NO3) 2 ethanol solution, and ultrahigh-temperature ceramic HfC nanowires (hereinafter referred to as HfCnw) are grafted through catalytic chemical deposition; and the SiC / HfC composite coating is prepared by a slurry brushing method. According to the PyC / HfCnw / HfC-SiC coating provided by the invention, the ceramic coating is subjected to cross-scale toughening / reinforcement through HfCnw, and meanwhile, the complementary advantages of the HfC-SiC composite coating in the aspects of oxidation resistance and ablation resistance are fully utilized, so that the mechanical properties, oxidation resistance and thermal shock resistance of the coating are improved, and the service life of C / C in a high-temperature oxygen-containing gas flow scouring environment is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of composite material coatings, and in particular relates to an ultra-high temperature ceramic nanowire toughened ultra-high temperature ablation-resistant coating and a preparation method thereof. Background Art

[0002] With the development of modern aerospace technology, space, with its unique geographical advantages and extremely important value in politics, economy, military and diplomacy, has been regarded by the world's military powers as a strategic high ground for maintaining national security and interests. Seizing the right to control space has become a common strategic goal of the world's aerospace powers.

[0003] C / C composite materials have a series of excellent properties such as low specific gravity, high specific strength, high specific modulus, low thermal expansion coefficient, and heat shock resistance. As rocket throat lining nozzles and aerospace vehicle thermal protection systems, they have advantages that are difficult to match with other materials. However, since C / C composite materials are composed of carbon matrix and reinforced carbon fibers, carbon is easily oxidized at high temperatures, and will oxidize rapidly above 400°C, resulting in a significant decrease in various properties. The easy oxidation characteristics of C / C composite materials seriously restrict their in-depth application in the aerospace and military fields. Moreover, with the continuous improvement of engine performance, the working environment of C / C composite materials has become increasingly harsh. In addition to the various static and dynamic loads required to be borne and transmitted, they must also withstand the high temperature, high pressure, high speed and ablation and scouring of the combustion gas flow containing a large number of condensed phase particles generated by the combustion of propellants, which places extremely stringent requirements on the performance of C / C composite materials. The inventors have found through research that in order to ensure that the excellent performance of C / C composite materials in a high-temperature aerobic environment can be fully utilized, protective measures must be taken to improve their antioxidant capacity. Ultra-high temperature ceramics are a series of high-temperature materials mainly composed of carbides, oxides, binary borides, and nitrides of insoluble metals such as Zr, Hf, and Ta. The melting point of such materials is generally around 3000°C and they can work above 2000°C. In addition, ultra-high temperature ceramics have good thermal stability, low linear expansion coefficient, large modulus, good oxidation resistance, and chemical corrosion resistance, and the strength does not vary too much at high temperatures. Therefore, applying them to high-temperature thermal protective coatings can greatly improve their high-temperature oxidation resistance. However, the traditional coating is not tightly bonded to the substrate, and there is a mismatch in the inherent thermal expansion coefficient, which leads to thermal mismatch residual stress during service, which may cause cracking and peeling of the coating under the scouring of airflow. Summary of the invention

[0004] In view of the above analysis, the present invention aims to provide a nanowire-reinforced ultrahigh temperature anti-ablation coating for C / C composite materials, which can significantly improve the anti-oxidation performance of C / C composite materials under oxygen-containing conditions and the bonding strength of the coating under scouring environments.

[0005] The present invention proposes an ultra-high temperature ceramic nanowire toughened ultra-high temperature ablation resistant coating and a preparation method. A layer of PyC inner coating is deposited on the C / C blank to improve the thermal mismatch problem between the substrate and the coating; and ultra-high temperature ceramic HfC is deposited on the PyC inner coating by catalytic CVD method. nw Finally, a SiC / HfC outer coating is prepared by brushing-cracking. nw The toughening effect on the outer coating improves the erosion resistance of the coating.

[0006] The object of the present invention is achieved through the following technical scheme: a nanowire toughened ultrahigh temperature ablation resistant coating, characterized in that it comprises a PyC inner coating prepared on the surface of a C / C blank, and a HfC prepared on the PyC inner coating. nw Toughened SiC / HfC composite outer coating. nw The toughened SiC / HfC composite coating includes HfC prepared on the PyC inner coating. nw and prepared in HfC nw SiC / HfC composite coating on.

[0007] Furthermore, the thickness of the PyC inner coating is 20-80 μm; nw The thickness of the toughened HfC / SiC composite outer coating is 80~220μm; Furthermore, the method for preparing the ultra-high temperature ceramic nanowire toughened ultra-high temperature ablation resistant coating comprises the following steps; S1: a layer of PyC inner coating is prepared on the surface of C / C body by isothermal CVD method; S2: Repeatedly brushing and drying Ni(NO3)2 ethanol solution on the PyC inner coating of the C / C blank coated with the PyC inner coating; S3: HfC is carried out on the C / C blank after repeated brushing and drying with Ni(NO3)2 ethanol solution. nw Deposition, HfC nw C / C; S4: Using the brushing-cracking process to deposit HfC nw SiC / HfC composite outer coating was prepared in vitro on C / C billet.

[0008] Furthermore, in S1, the density of the C / C body is 1.7-1.8 g / cm 3 ; Further, in S1, the process of preparing the PyC inner coating by isothermal CVD method is as follows: placing the C / C body into a deposition furnace, adjusting the position of the C / C body and the pores, and evacuating to below 200Pa; heating to 750~800℃ at 150~200℃ / min, and then heating to 1000~1100℃ at 50~60℃ / min, and starting to keep warm; introducing natural gas and nitrogen at a flow rate of 30~50L / min, maintaining the pressure in the furnace at 2~3KPa, and depositing for 30~40h; cooling down with the furnace after the deposition is completed to obtain a C / C body coated with the PyC inner coating; Further, in S2, the Ni(NO3)2 ethanol solution is used as a catalyst to catalyze the generation of HfC nw , the concentration is 0.01~0.02mol / L, the number of times of brushing and drying is 3~5 times, and the drying temperature is 60~80℃; Further, in S3, the HfC nw The deposition is carried out in a dual-temperature zone deposition furnace. The specific process is as follows: HfCl4 is placed in a clean porcelain boat and placed in the low-temperature zone of the deposition furnace; the C / C blank with Ni(NO3)2 attached to the surface is placed in the high-temperature zone of the deposition furnace, evacuated to below 200Pa, and H2 is introduced at a flow rate of 5~10L / min to maintain the pressure at 2~3KPa; the high-temperature zone is heated to 1000~1100℃ at 60~80℃ / h, and the low-temperature zone is heated to 250~300℃ at 60~80℃ / h before the high-temperature zone is heated to the target temperature for 1~2h; after the low-temperature zone is heated to the target temperature, the H2 flow rate is adjusted to 40~50L / min, and natural gas is introduced at 5~10L / min to start the deposition of HfC nw ; After 1~2h of deposition, stop introducing H2 and cool down the furnace to obtain surface grafted HfC nw C / C blank; Further, in S4, the slurry for painting is prepared by dispersing micron-sized Si powder and Hf powder in varnish, the mass ratio of micron-sized Si powder and Hf powder is (60-70%): (30-40%), and the volume ratio of powder and varnish is (30-40%): (60-70%), and the slurry preparation process is: sieve the micron-sized Si powder and Hf powder and mix them according to the mass ratio, add the varnish according to the set volume ratio, stir evenly and set aside; Furthermore, in S4, the cracking process of the coating-cracking process is carried out in a high-temperature cracking furnace, and the process parameters are: placing the C / C blank with the slurry coated on the surface in a high-temperature cracking furnace, evacuating to below 200 Pa, heating to 900~1000°C at 80~100°C / h, introducing Ar, and keeping warm for 20~40min; heating to 1600~1800°C at 50~60°C / h, and keeping warm for 3~4h; after the insulation is completed, the temperature is lowered with the furnace and taken out at below 100°C, and an ultra-high temperature ceramic nanowire-reinforced ultra-high temperature ablation-resistant coating is successfully prepared outside the C / C blank.

[0009] Compared with the prior art, the invention has the following beneficial effects: nw The cross-scale toughening / reinforcement of the ceramic coating effectively improves the mechanical properties of the coating. At the same time, the complementary advantages of the HfC-SiC composite coating in anti-oxidation and anti-ablation are fully utilized to improve the coating's anti-oxidation and thermal shock resistance, and to increase the service life of C / C in a high-temperature oxygen-containing gas erosion environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 It is a structural schematic diagram of the present invention. DETAILED DESCRIPTION

[0011] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without carrying out creative work are within the scope of protection of the present invention.

[0012] Technologies, methods, and apparatus known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, such technologies, methods, and apparatus should be considered part of the authorization specification.

[0013] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified. Example 1

[0014] An ultra-high temperature ceramic nanowire toughened ultra-high temperature ablation-resistant coating and a preparation method thereof, wherein the substrate of the coating is a C / C blank, and the coating comprises a PyC inner coating with a thickness of 20 mm and a HfC inner coating with a thickness of 220 mm. nw Toughened SiC / HfC composite outer coating.

[0015] The preparation method comprises the following steps: Firstly, the C / C body was pretreated. A piece of C / C body with a density of 1.72 was taken, and the surface was polished with 1000-mesh sandpaper. After ultrasonic treatment in ethanol, it was dried at 80°C for 3 h to remove the attached powder and oil stains.

[0016] The pretreated C / C body was placed in a vapor deposition furnace, the position of the C / C body and the pores was adjusted, and the vacuum was evacuated to 100Pa; the temperature was increased to 750℃ at 150℃ / min, and then to 1100℃ at 50℃ / min; after reaching 1100℃, natural gas and nitrogen with a volume ratio of 1:1 were introduced at a flow rate of 30L / min, the pressure in the furnace was maintained at 2KPa, and the temperature was kept for 30h; after the deposition was completed, the temperature was lowered along with the furnace, and it was taken out after it dropped to room temperature.

[0017] Prepare a Ni(NO3)2 ethanol solution with a concentration of 0.02 mol / L, apply the Ni(NO3)2 ethanol solution on the surface of the PyC inner coating with a brush, place it in an oven at 80°C for 3 hours, and repeat the application and drying 5 times to allow the surface of the PyC inner coating to adsorb enough Ni(NO3)2.

[0018] Take HfCl4 in a clean porcelain boat, wrap it with plastic wrap to prevent HfCl4 from deliquescing, and put it into the low temperature zone of the dual temperature zone deposition furnace; put the C / C blank with Ni(NO3)2 into the high temperature zone of the dual temperature zone deposition furnace, evacuate the deposition furnace to 100Pa, introduce H2 at a flow rate of 10L / min, and maintain the pressure at 2KPa; heat the high temperature zone to 1100℃ at 70℃ / h, and heat the low temperature zone to 250℃ at 80℃ / h before the high temperature zone is heated to the target temperature for 2h; after the low temperature zone is heated to the target temperature, adjust the H2 flow rate to 50L / min, and introduce natural gas at 10L / min to start depositing HfC nw ; After 2h of deposition, the H2 was stopped and the furnace was cooled to obtain surface grafted HfC nw C / C blank.

[0019] Sift the micron-grade Si powder and Hf powder with a purity of more than 99%, weigh Si powder and Hf powder according to a mass ratio of 7:3, mix them, add varnish according to a volume ratio of powder to varnish of 4:6, stir evenly, and then evenly apply it on the grafted HfC nw The surface of the C / C blank was raised to 220 mm, and the slurry was naturally dried. After the slurry had no fluidity, it was transferred to a high-temperature cracking furnace, evacuated to 100 Pa, heated to 1000 ° C at 100 ° C / h, introduced Ar, and kept warm for 30 min; heated to 1700 ° C at 50 ° C / h, and kept warm for 4 h; after the end of the heat preservation, the temperature was lowered with the furnace, and it was taken out after cooling to room temperature, and the PyC inner coating and HfC were obtained. nw Toughened (SiC-HfC) PyC-HfC with outer coating thickness of 40mm and 220mm respectivelynw / (SiC-HfC) composite coating. Example 2

[0020] An ultra-high temperature ceramic nanowire toughened ultra-high temperature ablation-resistant coating and a preparation method thereof, wherein the substrate of the coating is a C / C blank, and the coating comprises a PyC inner coating with a thickness of 50 mm and a HfC inner coating with a thickness of 160 mm. nw Toughened SiC / HfC composite outer coating.

[0021] The preparation method comprises the following steps: Firstly, the C / C body was pretreated. A piece of C / C body with a density of 1.78 was taken, and the surface was polished with 1000-mesh sandpaper. After ultrasonic treatment in ethanol, it was dried at 80°C for 3 h to remove the attached powder and oil stains.

[0022] The pretreated C / C body was placed in a vapor deposition furnace, the position of the C / C body and the pores was adjusted, and the vacuum was evacuated to 100Pa; the temperature was increased to 800℃ at 200℃ / min, and then to 1100℃ at 60℃ / min; after reaching 1100℃, natural gas and nitrogen with a volume ratio of 1:1 were introduced at a flow rate of 40L / min, the pressure in the furnace was maintained at 2KPa, and the temperature was kept for 30h; after the deposition was completed, the temperature was lowered along with the furnace, and it was taken out after it dropped to room temperature.

[0023] Prepare a Ni(NO3)2 ethanol solution with a concentration of 0.01 mol / L, apply the Ni(NO3)2 ethanol solution on the surface of the PyC inner coating with a brush, place it in an oven at 80°C for 3 hours, and repeat the application and drying 4 times to allow the PyC inner coating surface to adsorb enough Ni(NO3)2.

[0024] Take HfCl4 in a clean porcelain boat, wrap it with plastic wrap to prevent HfCl4 from deliquescing, and put it into the low temperature zone of the dual-temperature zone deposition furnace; put the green body with Ni(NO3)2 into the high temperature zone of the dual-temperature zone deposition furnace, evacuate the deposition furnace to 100Pa, introduce H2 at a flow rate of 5L / min, and maintain the pressure at 2KPa; heat the high temperature zone to 1100℃ at 70℃ / h, and heat the low temperature zone to 250℃ at 80℃ / h before the high temperature zone is heated to the target temperature for 2h; after the low temperature zone is heated to the target temperature, adjust the H2 flow rate to 40L / min, and introduce natural gas at 8L / min to start depositing HfC nw After 1.5 h of deposition, the H2 was stopped and the furnace was cooled to obtain surface grafted HfC nw C / C blank.

[0025] Sift the micron-grade Si powder and Hf powder with a purity of more than 99%, weigh Si powder and Hf powder according to a mass ratio of 6:4, mix them, add varnish according to a volume ratio of powder to varnish of 3:7, stir evenly, and then evenly apply it on the grafted HfCnw The surface of the C / C blank was 120 mm, dried naturally, and transferred to a high-temperature cracking furnace after the slurry had no fluidity, evacuated to 100 Pa, heated to 1000 ° C at 80 ° C / h, introduced Ar, and kept warm for 20 min; heated to 1700 ° C at 50 ° C / h, and kept warm for 3 h; after the end of the heat preservation, the temperature was cooled with the furnace, and it was taken out after cooling to room temperature, and the PyC inner coating and HfC were obtained. nw Toughened (SiC-HfC) PyC-HfC with outer coating thickness of 50mm and 160mm nw / (SiC-HfC) composite coating. Example 3

[0026] An ultra-high temperature ceramic nanowire toughened ultra-high temperature ablation-resistant coating and a preparation method thereof, wherein the substrate of the coating is a C / C blank, and the coating comprises a PyC inner coating with a thickness of 80 mm and a HfC inner coating with a thickness of 80 mm. nw Toughened SiC / HfC composite outer coating.

[0027] The preparation method comprises the following steps: Firstly, the C / C body was pretreated. A piece of C / C body with a density of 1.72 was taken, and the surface was polished with 1000-mesh sandpaper. After ultrasonic treatment in ethanol, it was dried at 80°C for 3 h to remove the attached powder and oil stains.

[0028] The pretreated C / C body was placed in a vapor deposition furnace, the position of the C / C body and the pores was adjusted, and the vacuum was evacuated to 100Pa; the temperature was increased to 750℃ at 150℃ / min, and then to 1100℃ at 50℃ / min; after reaching 1100℃, natural gas and nitrogen with a volume ratio of 1:1 were introduced at a flow rate of 50L / min, and the pressure in the furnace was maintained at 3KPa for 40h; after the deposition was completed, the temperature was lowered along with the furnace, and it was taken out after it dropped to room temperature.

[0029] Prepare a Ni(NO3)2 ethanol solution with a concentration of 0.01 mol / L, apply the Ni(NO3)2 ethanol solution on the surface of the PyC inner coating with a brush, place it in an oven at 80°C for 3 hours, and repeat the application and drying three times to allow the PyC inner coating surface to adsorb enough Ni(NO3)2.

[0030] Take HfCl4 in a clean porcelain boat, wrap it with plastic wrap to prevent HfCl4 from deliquescing, and put it into the low temperature zone of the dual temperature zone deposition furnace; put the C / C blank with Ni(NO3)2 into the high temperature zone of the dual temperature zone deposition furnace, evacuate the deposition furnace to 100Pa, introduce H2 at a flow rate of 10L / min, and maintain the pressure at 2KPa; heat the high temperature zone to 1100℃ at 70℃ / h, and heat the low temperature zone to 250℃ at 80℃ / h before the high temperature zone is heated to the target temperature for 2h; after the low temperature zone is heated to the target temperature, adjust the H2 flow rate to 40L / min, and introduce natural gas at 5L / min to start depositing HfC nw ; After 2h of deposition, the H2 was stopped and the furnace was cooled to obtain surface grafted HfC nw C / C blank.

[0031] Sift the micron-grade Si powder and Hf powder with a purity of more than 99%, weigh Si powder and Hf powder according to a mass ratio of 6:4, mix them, add varnish according to a volume ratio of powder to varnish of 3:7, stir evenly, and then evenly apply it on the grafted HfC nw The surface of the C / C blank was 80 mm, dried naturally, and after the slurry had no fluidity, it was transferred to a high-temperature cracking furnace, evacuated to 100 Pa, heated to 1000 ° C at 100 ° C / h, introduced Ar, and kept warm for 30 min; heated to 1700 ° C at 50 ° C / h, and kept warm for 4 h; after the insulation was completed, the temperature was cooled with the furnace, and it was taken out after cooling to room temperature, and the PyC inner coating and HfC were obtained. nw Toughened (SiC-HfC) outer coating thickness is 80mm and PyC-HfC is 80mm nw / (SiC-HfC) composite coating.

[0032] Table 1 Statistics of test results of ultra-high temperature ceramic nanowire toughened ultra-high temperature anti-ablation coating Example Example 1 Example 2 Example 3 1400℃400h static oxidation weight loss rate (%) -4.47 -5.92 -4.86 Bonding strength (MPa) 8.543 6.229 5.324 Plasma line ablation rate (mm / s) 0.0083 0.0092 0.0105 In addition to the parameters in the preparation process involved in the above-mentioned embodiments 1 to 3, it is also feasible to select other preparation parameters.

[0033] The protection scope of the present invention is not limited to the above embodiments. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be included in the protection scope of the present invention.

Claims

1. A nanowire toughened ultra-high temperature ablation-resistant coating, characterized in that: The invention comprises a PyC inner coating prepared on the surface of a C / C body, and a HfC inner coating prepared on the PyC inner coating. nw Toughened SiC / HfC composite outer coating; The HfC nw The toughened SiC / HfC composite coating includes HfC prepared on the PyC inner coating. nw and prepared in HfC nw SiC / HfC composite coating on.

2. The nanowire toughened ultrahigh temperature ablation resistant coating according to claim 1, characterized in that: The thickness of the PyC inner coating is 20-80 μm; nw The thickness of the toughened HfC / SiC composite outer coating is 80~220μm.

3. A method for preparing a nanowire toughened ultrahigh temperature ablation resistant coating, characterized in that: It includes the following steps: S1: a layer of PyC inner coating is prepared on the surface of C / C body by isothermal CVD method; S2: Repeatedly brushing and drying Ni(NO3)2 ethanol solution on the PyC inner coating of the C / C body coated with the PyC inner coating to obtain a C / C body with Ni(NO3)2 attached on the surface; S3: HfC treatment of C / C blank with Ni(NO3)2 on the surface nw Deposition to obtain surface grafted HfC nw C / C blank; S4: Grafting HfC on the surface using a brushing-pyrolysis process nw SiC / HfC composite coating was prepared on C / C blank.

4. The method for preparing a nanowire toughened ultrahigh temperature ablation resistant coating according to claim 3, characterized in that: In S1, the density of C / C body is 1.7~1.8g / cm 3 .

5. The method for preparing a nanowire toughened ultrahigh temperature ablation resistant coating according to claim 3, characterized in that: In S1, the process of preparing the PyC inner coating by isothermal CVD method is as follows: placing the C / C blank into a deposition furnace, adjusting the position of the C / C blank and the pores, and evacuating to below 200Pa; heating to 750~800℃ at 150~200℃ / min, and then heating to 1000~1100℃ at 50~60℃ / min, and starting to keep warm; introducing natural gas and nitrogen with a volume ratio of 1:1 at a flow rate of 30~50L / min, maintaining the pressure in the furnace at 2~3KPa, and depositing for 30~40h; after the deposition is completed, the temperature is lowered along with the furnace to obtain a C / C blank coated with a PyC inner coating.

6. The method for preparing a nanowire toughened ultrahigh temperature ablation resistant coating according to claim 3, characterized in that: In S2, the Ni(NO3)2 ethanol solution is used as a catalyst to catalyze the generation of HfC nw The concentration of the Ni(NO3)2 ethanol solution is 0.01-0.02 mol / L, and the number of times of brushing and drying is 3-5 times.

7. The method for preparing a nanowire toughened ultrahigh temperature ablation resistant coating according to claim 3, characterized in that: In S3, the HfC nw The deposition is carried out in a dual-temperature zone deposition furnace. The specific process is as follows: HfCl4 is placed in a clean porcelain boat and placed in the low-temperature zone of the deposition furnace; the C / C blank with Ni(NO3)2 attached to the surface is placed in the high-temperature zone of the deposition furnace, evacuated to below 200Pa, and H2 is introduced at a flow rate of 5~10L / min to maintain the pressure at 2~3KPa; the high-temperature zone is heated to 1000~1100℃ at 60~80℃ / h, and the low-temperature zone is heated to 250~300℃ at 60~80℃ / h before the high-temperature zone is heated to the target temperature for 1~2h; after the low-temperature zone is heated to the target temperature, the H2 flow rate is adjusted to 40~50L / min, and natural gas is introduced at 5~10L / min to start the deposition of HfC nw ; After 1~2h of deposition, stop introducing H2 and cool down the furnace to obtain surface grafted HfC nw C / C blank.

8. The method for preparing a nanowire toughened ultrahigh temperature ablation resistant coating according to claim 3, characterized in that: In S4, the slurry for brushing is prepared by dispersing powder in varnish, and the volume ratio of powder to varnish is (30~40%): (60~70%), and the powder is composed of micron-sized Si powder and Hf powder in a mass ratio of (60~70%): (30~40%).

9. The method for preparing a nanowire toughened ultrahigh temperature ablation resistant coating according to claim 8, characterized in that: The preparation process of the slurry is as follows: sieve micron-grade Si powder and Hf powder, mix them according to a mass ratio, add varnish according to a set volume ratio, stir evenly and set aside.

10. The method for preparing a nanowire toughened ultrahigh temperature ablation resistant coating according to claim 8, characterized in that: In S4, the cracking process of the coating-cracking process is carried out in a high-temperature cracking furnace, and the process parameters are: placing the C / C blank with the slurry on the surface in a high-temperature cracking furnace, evacuating to below 200 Pa, heating to 900~1000°C at 80~100°C / h, introducing Ar, and keeping warm for 20~40min; heating to 1600~1800°C at 50~60°C / h, and keeping warm for 3~4h; after the insulation is completed, the temperature is lowered with the furnace, taken out below 100°C, and a nanowire-toughened ultra-high temperature anti-ablation coating is prepared outside the C / C blank.

Citation Information

Patent Citations

  • Preparation method of HfC-SiC modified carbon / carbon composite material

    CN103936464A

  • Hafnium carbide nanowire-toughened ceramic coating layer of surface of carbon / carbon composites and preparation method thereof

    CN103951470A

  • HfC nanowire-toughened anti-ablation ceramic coating on surface of carbon / carbon composite material and preparation method

    CN106673710A

  • Core-shell structure toughened (Hf, Ta) C solid solution superhigh-temperature ceramic coating and one-step preparation method

    CN115403397A

  • Chceking method for multi-article delivery and delivery system thereof

    KR1020200087520A

Cited By

  • Ceramic coating based on nanocarbon in-situ conversion toughening and preparation method thereof

    CN121850735A